El calculo del agua precipitable y algunas de sus aplicaciones en Argentina - Catuogno, Graciela A. (1997)
Different models have been essayed for the estimation ofprecipitable water based on humidity data observed at ground level in order to improve the spatial and time distribution of precipitable water values, due to the fact that there are only four upper air data stations in an extended area of central and northeastern Argentina. Fields of precipitable water are analysed in relation to the development of mesoscale convective complexes. Ten years of data were processed in order to evaluate the different models. One model used only surface dew point in an adiabatic saturate atmosphere calculated from that value. The vertical profile ofthe dew point monthly average was used as an alternate method for calculating the precipitable water, modified in the layer between the surface and 800 hpa. by the average surface dew point gradient. When the results ofthe first model were compared with the values of precipitable water calculated with radiosonde data it showed a seasonal behaviour in the error estimation which reached 30% during summer. Results improved when a second method was applied. The analysis of precipitable water model showed a redistribution ofwater vapour in the atmosphere during the evolution ofmesoscale convective complexes according to our expectation. The precipitable water field appears as an upper limit of the areal precipitation in the zone, existing exceptions for punctual cases.